Το Βυζάντιο και οι Ιωαννίτες Ιππότες της Ρόδου (1306-1409) - LUTTRELL, Anthony (Byzantina Symmeikta, 1997)
Anthony Luttrell The Hospitallers of Rhodes and Byzantium (1306-1409) The Hospital of Saint John of Jerusalem constituted a Latin military order composed of professed religious who took vows of poverty, chastity and obedience, and who were devoted to a holy war against the infidel. In 1306 they occupied Rhodes and provided its Greek inhabitants with reasonable security, prosperity and a degree of religious freedom. Rhodes became a base for attacks on the neighbouring Turkish emirates and, after about 1358, for more distant campaigns against the Ottomans in mainland Greece and elsewhere. From about 1390 to 1409 the Hospitallers collaborated with Byzantine rulers, especially in the years after 1396 when they defended Corinth and the Despotate of the Morea against the Turks. Thereafter contacts between Rhodes and Constantinople became infrequent.